2018
DOI: 10.21873/invivo.11216
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Bladder Cancer Undergoing Ileal Conduit: A Comparison of Women Versus Men

Abstract: Abstract. Background/Aim: Studies comparing healthrelated quality of life (HR-QoLBladder cancer is one of the most commonly diagnosed types of cancer and Europe has the highest incidence rate of bladder cancer worldwide. Morevover, Spain and Italy have the highest incidence in men in Europe, at approximately 37/100,000 and 33/100,000. respectively, (1). Classically, according to European Association of Urology (EAU) Guidelines, radical cystectomy (RC) represents the gold standard treatment for muscle-invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
(8 reference statements)
1
15
0
Order By: Relevance
“…Using FSFI, after an initial worsening of the results over the first 3 months after surgery, it is possible to denote a significant improvement at 12 months of follow-up, even if in comparison with the baseline the results remain significantly reduced. These results support what was already highlighted by Bhatt et al [53] in their study on a subset of women who underwent RC with neurovascular preservation and ONB. They found that FSFI score could be preserved compared with women who did not undergo NS, who had a significant decline.…”
Section: Discussionsupporting
confidence: 92%
“…Using FSFI, after an initial worsening of the results over the first 3 months after surgery, it is possible to denote a significant improvement at 12 months of follow-up, even if in comparison with the baseline the results remain significantly reduced. These results support what was already highlighted by Bhatt et al [53] in their study on a subset of women who underwent RC with neurovascular preservation and ONB. They found that FSFI score could be preserved compared with women who did not undergo NS, who had a significant decline.…”
Section: Discussionsupporting
confidence: 92%
“…QoL was assessed by EORTC QLQ-C30 and EORTC BLM-30. The female patients were 33, and they presented significantly greater problems than men in cognitive functioning and in future perspective [ 33 ].…”
Section: Measurement Of Quality Of Lifementioning
confidence: 99%
“…Recently, the paper by Siracusano and co-workers focusing on the differences between male and female bladder cancer patients, compared 112 men vs. 33 women, and although the two groups were comparable in terms of clinical and demographical variables, the differences in the overall QoL were significantly worse for women than for men, but when specifically enquired about their sexual life, men had more problems in sexual functioning, and in general sexual satisfaction, than women [ 33 ].…”
Section: Measurement Of Quality Of Lifementioning
confidence: 99%
“…They reported that in these recurrence-free women with long-term follow-up, patients with cutaneous ureterostomy reported a worse HRQOL compared to women with either ileal conduits or orthotopic neobladders [24]. Siracusano et al [25] reported that female patients who underwent ileal conduit presented a greater burden than male patients in cognitive functioning as well in future perspective, but lower concerns regarding sexual function. To better evaluate the quality of life, especially in patients with radical cystectomy, several questionnaires have been developed, some of which have been implemented in clinical care [26, 27].…”
Section: Discussionmentioning
confidence: 99%